2021
DOI: 10.3390/cancers13020193
|View full text |Cite
|
Sign up to set email alerts
|

MRI-Based Radiomics Input for Prediction of 2-Year Disease Recurrence in Anal Squamous Cell Carcinoma

Abstract: Purpose: Chemo-radiotherapy (CRT) is the standard treatment for non-metastatic anal squamous cell carcinomas (ASCC). Despite excellent results for T1-2 stages, relapses still occur in around 35% of locally advanced tumors. Recent strategies focus on treatment intensification, but could benefit from a better patient selection. Our goal was to assess the prognostic value of pre-therapeutic MRI radiomics on 2-year disease control (DC). Methods: We retrospectively selected patients with non-metastatic ASCC treated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…From these twelve full texts, a total of nine studies met the inclusion criteria and were included in our analysis. [16][17][18][19][20][21][22][23][24] See Figure 1.…”
Section: Search Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…From these twelve full texts, a total of nine studies met the inclusion criteria and were included in our analysis. [16][17][18][19][20][21][22][23][24] See Figure 1.…”
Section: Search Resultsmentioning
confidence: 99%
“…The amalgamation of these novel parameters with pre-existing clinical factors appears to augment performance. 16,17,22,23 This is precisely where the prowess of machine learning (ML) algorithms becomes evident, having already demonstrated remarkable accomplishments across various cancer categories. [32][33][34][35] A proportion of ASCC patients undergoing curative CRT still require salvage abdominoperineal resection (APR) due to inadequate treatment response or local recurrence.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A study found that Kurtosis combined with several clinical and other texture parameters could predict eight-year event-free survival (EFS) in Luminal Non-Metastatic Breast Valencia ( 33 ). In addition to adenocarcinoma, another study on anal squamous cell carcinoma also found that Entropy and Joint Energy can be independent risk factors for predicting tumor recurrence rate ( 34 ). Therefore, the radiomics indicators screened in this study are not only reproducible in the evaluation of multiple biological characteristics and prognosis of endometrial cancer, but also seem to be similar in other tumors.…”
Section: Discussionmentioning
confidence: 99%